Electrotaxis-on-Chip to Quantify Neutrophil Migration Towards Electrochemical Gradients - Moarefian, Maryam; Davalos, Rafael V.; Burton, Michael D.; Jones, Caroline N. (Frontiers in Immunology, 2021)
Electric fields are generated in vivo in a variety of physiologic and pathologic settings, including wound healing and immune response to injuries to epithelial barriers. Electrotaxis is the guided migration of cells along electric field gradients, and has previously been reported. However, there remains a need for engineering tools with high spatial and temporal resolution to quantify EF guided migration. Here we report the development of an electrotaxis-on-chip (ETOC) platform that enables the quantification of dHL-60 cell, a model neutrophil-like cell line, migration toward both electrical and chemoattractant gradients. Neutrophils are the most abundant white blood cells and set the stage for the magnitude of the immune response. Therefore, developing engineering tools to direct neutrophil migration patterns has applications in both infectious disease and inflammatory disorders. The ETOC developed in this study has embedded electrodes and four migration zones connected to a central cell-loading chamber with migration channels [10 µm X 10 µm] and enables both parallel and competing chemoattractant and electric field gradients. We use our novel ETOC platform to investigate dHL-60 cell migration in three biologically relevant conditions: 1) in a DC electric field; 2) parallel chemical and electric field gradients; and 3) perpendicular chemical and electric field gradient. We first quantified effects of electric field intensities (0.4V/cm-1V/cm) on dHL-60 cell electrotaxis. In the second scenario, we tested whether it was possible to increase dHL-60 cell migration to a bacterial signal (N-formylated peptides) by adding a parallel electric field. There was significant increase (6-fold increase) in dHL60 migration toward fMLP and cathode of DC electric field (0.6V/cm, n=4, p-value<0.005) vs. fMLP alone. Finally, we evaluated whether we could decrease or re-direct dHL-60 cell migration away from an inflammatory signal (leukotriene B4) and showed a ~2.9-fold decrease of dHL60s toward LTB4 vs. LTB4 alone. The magnitude and direction of the electric field can be more precisely and quickly changed than most other guidance cues such as chemical cues in clinical investigation. A better understanding of EF guided cell migration will enable the development of new EF-based treatments to precisely direct immune cell migration to treat inflammatory disorders.